Monitoring Power Meter terhadap Power Faktor Berbasis Modbus Master Simulator - Wibowo, Sunu Hasta; Suriansyah, Bambang; Rachman, Syaiful (Jurnal Teknologi, 2024)
In this study, the emphasis is on a power meter, a device that already has the ability to display measurements of electrical energy usage. This power meter is very useful for monitoring the amount of electrical energy used, and there are various parameters of electrical energy used such as voltage (V), energy (Kwh), current (A), reactive power (Kvar), power factor (pf), power (Watt), and others. Currently, the common monitoring system is a monitoring system that uses a power energy meter as a medium for reading electrical quantities and its visual display. So to monitor the electrical panel to analyze the power factor (pf) against performance in the laboratory room, this study uses a power meter type PM 1200 based on the Modbus Master Simulator to be able to display visually and in real time, in order to ease the task of recording data manually. So that the results are obtained with different power factors (pf) when the electrical load changes in the room, with a power factor of 0.9644 and 0.576 with different electrical loads.